2010
DOI: 10.1099/mic.0.041566-0
|View full text |Cite
|
Sign up to set email alerts
|

Small subunits of RNA polymerase: localization, levels and implications for core enzyme composition

Abstract: Bacterial RNA polymerases (RNAPs) contain several small auxiliary subunits known to co-purify with the core a, b and b9 subunits. The v subunit is conserved between Gram-positive and Gramnegative bacteria, while the d subunit is conserved within, but restricted to, Gram-positive bacteria. Although various functions have been assigned to these subunits via in vitro assays, very little is known about their in vivo roles. In this work we constructed a pair of vectors to investigate the subcellular localization of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 47 publications
1
38
0
Order By: Relevance
“…They contain an additional subunit, d, which is encoded by the rpoE gene in the model organism Bacillus subtilis. [1] Previously, the d subunit was reported to increase the specificity of RNAP for a promoter sequence, [2,3] and, recently, we reported that the d subunit is involved in regulation of transcription initiation in response to the concentration of the initiating nucleoside triphosphate (iNTP). [4] The d subunit destabilizes the open complex, a crucial intermediate of transcription initiation.…”
Section: Introductionmentioning
confidence: 99%
“…They contain an additional subunit, d, which is encoded by the rpoE gene in the model organism Bacillus subtilis. [1] Previously, the d subunit was reported to increase the specificity of RNAP for a promoter sequence, [2,3] and, recently, we reported that the d subunit is involved in regulation of transcription initiation in response to the concentration of the initiating nucleoside triphosphate (iNTP). [4] The d subunit destabilizes the open complex, a crucial intermediate of transcription initiation.…”
Section: Introductionmentioning
confidence: 99%
“…The NTD contains four ␣-helices and an antiparallel ␤-sheet (7). Delta binds to RNAP in vivo (8), but the binding site is unknown.…”
mentioning
confidence: 99%
“…While there are highly conserved subunits of RNAP across the kingdoms, within the Firmicutes we now know that there are at least two additional small subunits of RNAP, giving a subunit composition of ␣ 2 ␤␤=␦ε in these organisms. The ␦, ε, and subunits all appear to be present at levels similar to those of the other subunits of RNAP (6,17), suggesting that they are all core subunit components.…”
Section: Discussionmentioning
confidence: 90%